Engineering the sialome of mammalian cells with sialic acid mimetics - Daniël L.A.H. Hornikx; Eline A. Visser; Venetia Psomiadou; Christian Büll; Thomas J. Boltje (STAR Protocols, 2023)
Summary: Mammalian glycans show a diversity in sialic acid capping, constituting the sialome. Sialic acids can be extensively modified chemically, yielding sialic acid mimetics (SAMs). Here, we present a protocol for detecting and quantifying incorporative SAMs using microscopy and flow cytometry, respectively. We detail steps for linking SAMS to proteins with western blotting. Lastly, we detail procedures for incorporative or inhibitory SAMs and how SAMs can be used for the on-cell synthesis of high-affinity Siglec ligands.For complete details on the use and execution of this protocol, please refer to Büll et al.1 and Moons et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.